Requirements for the information on reference standards submitted in the dossier for biologicals - R. A. Volkova; O. V. Fadeikina; O. B. Ustinnikova; K. A. Sarkisyan; A. A. Movsesyants; V. A. Merkulov; V. V. Kosenko (Биопрепараты: Профилактика, диагностика, лечение, 2024)
SCIENTIFIC RELEVANCE. The use of appropriately certified reference standards (RSs) is a necessary element of analytical procedure standardisation that ensures comparability of results across different laboratories assessing the quality of medicines, which is important for the quality control of biologicals. Marketing authorisation involves providing information on RSs, but no specific requirements are given for the relevant section of the dossier. Therefore, it is necessary to develop the requirements for the appropriate guidelines.AIM. This study aimed to develop specific requirements for the materials that should be included in the Reference Standards section of the dossier for a biological product.DISCUSSION. The authors analysed national and international regulatory frameworks governing RSs for biologicals, including documents by the World Health Organisation (WHO), the Eurasian Economic Union, the International Organisation for Standardisation (ISO), and the Russian Federal Agency for Technical Regulation and Metrology. Additionally, the authors analysed the experience of RS certification and use at the Scientific Centre for Expert Evaluation of Medicinal Products. This article covers specific aspects of biological RS certification, considering the differences between measurement techniques and analytical procedures. The authors formulated the key requirements for the documents submitted in the dossier section on RSs for biologicals (biological reference materials). The methods (analytical procedures) used for RS certification should be described in accordance with the requirements for standard operating procedures. Adequate validation studies should establish the necessary validation characteristics of these analytical procedures. Additionally, this article presents the requirements developed to certify primary RSs for structure confirmation of proteins in novel biologicals. The values of certified characteristics and critical quality indicators should be established, and the RS production technology should be described and in compliance with WHO recommendations and/or Good Manufacturing Practice (GMP) standards. The basic certification stages are common to all types of RSs. The RS shelf life should be established in real-time stability studies, whereas accelerated stability testing may be useful for studying degradation mechanisms and the effects of short-term deviations from the specified storage conditions. In accordance with WHO recommendations, the Reference Standards section of the registration dossier should specify changes to the RS that require regulatory approval.CONCLUSIONS. The authors believe that the requirements for the materials in the Reference Standards section of the dossier for a biological product, as systematised in this study for inclusion in the relevant guidelines, will provide a unified approach to RS development, certification, and documentation for applicants, developers, and competent authority experts and will streamline RS consideration during marketing authorisation.